Discursive reactions to populism: The case of the European Central Bank - Oanca, Alexandra (Journal of Danubian Studies and Research, 2022)
This study examines the discursive reactions of the European Central Bank (ECB) to populism. Focusing on the period from 2012 to 2019, the research uses a corpus of 20 speeches delivered by ECB representatives. Through a textual and contextual analysis, the aim is to uncover patterns and themes within the ECB’s discourse on populism. The findings reveal a cohesive and unified discourse, suggesting a consistent messaging strategy employed by the ECB. The discourse strand is shown to be predominantly anti-populist, portraying populism as a referential object and associating it with economic uncertainty. The two possible explanations for the ECB’s anti-populist discourse are proposed: as part of the ECB’s discursive strategy to legitimise its actions and reinforce credibility, or as a sign of the potential politicisation of the bank.